Optimization on Preventive Maintenance and Spare Unit Number for Multi-unit Parallel System. Issue 1 (May 2020) - Gao, Wenke; Yang, Tianshu; Chen, Xufeng; Liang, Xin
Abstract: Preventive maintenance (PM) for multi-unit parallel system with limited production resource is a crucial issue. To find a solution for the issue, this study focused on a multi-unit parallel system with one repairman and some spare units, and developed an optimization model for the system. In the model, PM policy and cold spare unit number were jointly considered. After optimization, an optimal PM policy with PM interval of running and spare units, PM number and cold spare unit number were obtained. Then, a numerical example was analyzed to illustrate the proposed model, and some results were attained based on the sensitive analysis.